Exploring community-dwelling stroke survivors' experiences of receiving a nurse-led theory-based stroke self-management programme: A qualitative study. Issue 37 (17th September 2021) - Lo, Suzanne Hoi Shan; Chau, Janita Pak Chun
Abstract : Abstract: International evidence-based guidelines recommend self-management support for stroke survivors to improve their health outcomes. We developed a 4-week nurse-led stroke self-management programme (SSMP) and conducted a randomised controlled trial to assess its effects. This paper reports the findings of a qualitative study nested within the randomised controlled trial to explore stroke survivors' experiences of SSMP participation. Semi-structured interviews were conducted with all adult participants who were clinically diagnosed with a first or recurrent ischaemic or haemorrhagic stroke, residing at home, communicable in Cantonese, had a Montreal Cognitive Assessment score below the second percentile, and participated in at least 1 SSMP session. All interviews were conducted in Cantonese, lasted approximately 45 minutes, and were audio-recorded. Interview data were transcribed verbatim and analysed thematically. Sixty-four stroke survivors (mean age 66.33 years, SD 12.34) were recruited, and 59 were interviewed via phone immediately after completion of SSMP. Three themes were derived. Overall, participants were satisfied with the SSMP. Their understanding of self-management was improved, and they recognised its importance in recovery. Their confidence in self-management was also enhanced through the use of multifaceted strategies. Suggestions were made to enhance their participation experiences, including increased home visits and group sessions, making group session attendance optional and arranging them more accessibly, meeting the survivors who shared their survival experiences in the videos, and access to the videos online. This study concurred that the SSMP enhanced stroke survivors' self-efficacy in self-management. Rearrangement of the programme format and enhancements in accessibility could be further examined to enable more effective stroke self-management.